Morning versus evening supplementation for heifers grazing winter range - Vanzant, E.; Cochran, B.; Corah, L.; Zoellner, K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Supplementing developing heifers in the morning was compared with supplementation at sundown. No difference was evident among treatments in average daily gain, distance traveled, or time spent grazing.
Keywords: Beef; Morning vs. evening grazing; Heifers